Just kids - Smith, Patti (London Bloomsbury, 2010)
In this memoir, singer-songwriter Patti Smith shares tales of New York City : the denizens of Max's Kansas City, the Hotel Chelsea, Scribner's, Brentano's and Strand bookstores and her new life in Brooklyn with a young man named Robert Mapplethorpe--the man who changed her life with his love, friendship, and genius.
Monday's children -- Just kids -- Hotel Chelsea -- Separate ways together -- Holding hands with God.
UCWS-2013-G-1482 donated by Laurindo Garcia
Keywords: Smith, Patti; Mapplethorpe, Robert; Chelsea Hotel -- Biography; Women rock musicians -- United States -- Biography; Photographers -- United States -- Biography; Women poets -- 20th century -- Biography; Poets, American -- 20th century -- Biography; Artists -- New York (State) -- New York -- Biography; Musicians -- New York (State) -- New York -- Biography; New York (N.Y.) -- Biography